2020
DOI: 10.1021/acs.jctc.0c00445
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Subdiffusive Solute Dynamics and Predicting Selectivity in Nanoscale Pores with Time Series Modeling

Abstract: Fitting mathematical models with a direct connection to experimental observables to the outputs of molecular simulations can be a powerful tool for extracting important physical information from them. In this study, we present two new approaches that use stochastic time series modeling to predict long-time-scale behavior and macroscopic properties from molecular simulation, which can be generalized to other molecular systems where complex diffusion occurs. In our previous work, we studied long molecular dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In our previous work, we showed that in systems without convective flux, such as our MD simulations, selectivity toward component i over j is simply: where J is solute flux and ΔC is the trans-membrane concentration difference . The concentrations of solutes are the same across our simulations, therefore eq reduces to the ratio of solute fluxes.…”
Section: Methodsmentioning
confidence: 79%
See 4 more Smart Citations
“…In our previous work, we showed that in systems without convective flux, such as our MD simulations, selectivity toward component i over j is simply: where J is solute flux and ΔC is the trans-membrane concentration difference . The concentrations of solutes are the same across our simulations, therefore eq reduces to the ratio of solute fluxes.…”
Section: Methodsmentioning
confidence: 79%
“…11 Based on the chemical intuition gained from our previous qualitative MD studies of solute transport in an H II phase LLC membrane, we have contributed our own stochastic modeling approaches with goals similar to both TEKMC and DBP. 7,12 In previous studies, we identified three classes of trapping behavior which result in subdiffusion out to the microsecond time scale. In our first approach to stochastically model this behavior, we treated the system's dynamics as a sequence of anticorrelated hops between power law distributed periods of entrapment, a framework called subordinated fractional Brownian or Levy motion.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations